2020
DOI: 10.1002/jmv.25770
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of clinical laboratory data determinations for patients with the severe COVID‐19

Abstract: The role of clinical laboratory data in the differential diagnosis of the severe forms of COVID-19 has not been definitely established. The aim of this study was to look for the warning index in severe COVID-19 patients. We investigated 43 adult patients with COVID-19. The patients were classified into mild group (28 patients) and severe group (15 patients). A comparison of the hematological parameters between the mild and severe groups showed significant differences in interleukin-6 (IL-6), D-dimer (D-D), glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

78
875
11
63

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 923 publications
(1,027 citation statements)
references
References 8 publications
(10 reference statements)
78
875
11
63
Order By: Relevance
“…As in line with the high prevalence of multi-organ failure, high d-dimer levels, fibrinogen and prolonged thrombin time were seen in severe diseases (17). fatality rate of 7.2% (15, 18), which was three times as high as the one in China.…”
Section: Epidemiological Data Of Covid-19mentioning
confidence: 72%
“…As in line with the high prevalence of multi-organ failure, high d-dimer levels, fibrinogen and prolonged thrombin time were seen in severe diseases (17). fatality rate of 7.2% (15, 18), which was three times as high as the one in China.…”
Section: Epidemiological Data Of Covid-19mentioning
confidence: 72%
“…Data related to other tests are less certain and often contradictory (24,25). Disease severity is variably associated with prolongation of the prothrombin time (PT) and international normalized ratio (INR) (1,20,26), and thrombin time (TT) (27), and variably by a trend toward shortened activated partial thromboplastin time (aPTT) (1,16,19,28). Recently, Tang et al (7) assessed 183 patients with COVID-19, 21 of whom (11.5%) died.…”
Section: Covid-19 and Hemostasis Parametersmentioning
confidence: 99%
“…We initially identified 73 articles based on our search strategy, 64 of which were excluded after title, abstract, or full-text reading, because they were review articles, did not report IL-6 levels, or did not classify the condition of COVID-19 patients as non-severe and severe. Finally, only nine studies were included in this meta-analysis [1][2][3][4][5][6][7][8][9]. Although the heterogeneity was considerably high (I 2 = 89%; P < 0.00001), we observed that IL-6 levels were significantly increased in COVID-19-infected patients with severe condition compared with those with non-severe condition (SMD = 0.71, 95%CI −0.31-1.12, P = 0.0005) ( Fig.…”
Section: Disponible En Ligne Surmentioning
confidence: 99%